Cerebrospinal fluid flow behaviour in lumbar spinal stenosis - a computational fluid dynamic study based on magnetic resonance imaging - Liang, Tie Teck (2018)
Introduction Degenerative lumbar spinal stenosis (LSS) is a pathology characterized by compression of neural elements and vascular structures due to a narrowed lumbar spinal canal. The main clinical presentation is neurogenic claudication. The pathophysiology is not entirely understood. Often, the clinical manifestation is not corresponding to the finding in magnetic resonance images (MRI). Objective The aim of this study is to determine the behaviour of cerebrospinal fluid (CSF) flow in degenerative LSS by using computational fluid dynamic (CFD) simulation through the qualitative and quantitative prediction of fluid flow and comparing with the flow in the normal spine. Methods This cross-sectional study evaluated the selected 34 MRI images, which had fulfilled the inclusion and exclusion criteria. The T2 weighted MRI images were used to assess the level and degree of stenosis. These images were transferred electronically to MIMIC and SOLIDWORKS for model generation and then to ANSYS FLUENT for the CFD simulations with the predetermined boundary condition. Lastly, the results were extracted according to the region of interest (ROI). Results The mean velocity in stenosis groups at L3/L4 disc level and L4/L5 disc level was relatively lower than the normal group, but it was higher at the L5/S1 disc level for the stenosis groups. This study revealed an insignificant difference between the normal groups and the stenosis groups at L3/L4 disc level. However, significant differences between the stenosis group and the normal group at L4/L5 disc level (p < 0.001) and L5/S1 disc level (p < 0.001) were reported. This study demonstrated the severity of stenosis did not carry a great influence toward the CSF velocity. The mean pressure of the CSF reduced from L3/L4 disc level to L5/S1 disc level. The mean pressure in the normal group was ranging from 981.47 Pa to 982.29 Pa, but for stenosis group was ranging from 981.00 Pa to 983.00 Pa, depending on the stenosis level. The mean wall shear stress (WSS) in normal group was 0.019 Pa, and stenosis group was ranging 0.014 Pa to 0.024 Pa at L3/L4 disc level. However, indifferent mean WSS was showed at the L4/L5, and L5/S1 disc level revealed the (0.011 Pa and 0.007 Pa, respectively) for both normal and stenosis groups. All the streamlines demonstrated a laminar flow pattern regardless the normal spine or stenotic spine with their Reynold’s number ranging from 326.2 to 1312.57. Conclusion The mean velocity in degenerative LSS did not differ significantly in stenosis group compared to the normal group at L3/L4 disc leve, but the study showed the mean velocity differ significantly for L4/L5 disc level and L5/S1 disc level. The degree of stenosis did not influence significantly on the mean velocity. The mean pressure reduced when flowed caudally, and showed insignificant different. Insignificant different was showed in the mean WSS as well as the flow pattern between the normal groups and degenerative LSS groups.